Nutritional, Chemical, Antioxidant and Antibacterial Screening of Astragalus cicer L. and Astragalus glycyphyllos L. Different Morphological Parts - Saba Shahrivari-Baviloliaei; Agnieszka Konopacka; Liege Aguiar Pascoalino; Filipa Reis; Dawid Kunkowski; Spyridon A. Petropoulos; Pawel Konieczynski; Ilkay Erdogan Orhan; Alina Plenis; Agnieszka Viapiana (Foods)
The chemical composition and biological activity of A. glycyphylos and A. cicer are scarcely investigated. In this study, the nutritional and chemical profiles of A. cicer and A. glycyphyllos, considering their different morphological parts (leaves, fruits and roots), were assessed together with their antioxidant and antibacterial potential. Our results showed that carbohydrates are the major macronutrients in both Astragalus species (above 62 g/100 g dry weight—DW). High amounts of ash (above 4.6 g/100 g DW) and protein (above 13.0 g/100 g DW) were also identified, particularly in leaves and fruits of A. cicer and A. glycyphyllos. Moreover, A. cicer was richer in sugars than A. glycyphyllos, while roots of both Astragalus species were the richest of fatty acids. Ten phenolic compounds were identified, with gallic acid and quercetin being predominant, above 49.84 and 37.27 μg/g DW, respectively. The mineral analysis revealed zinc and iron as the major constituents. Regarding the plants’ antioxidant and antibacterial activity, both Astragalus species had antioxidant potential, and their water extracts showed antibacterial activity against S. aureus and E. coli. Altogether, these results provide insight into the potential of A. glycyphyllos and A. cicer as a source of nutritional benefits and active phytochemicals for many people, and they can be applied in the food sector as foods and as promising sources of natural ingredients.